Análise do campo de tensões de contato em um substrato plano revestido - Duarte, Écio Naves (2003)
To coat mechanical components, that will be subjected to contact load, has been a procedure aiming the reduction of the wearing in the substrate. However, these components could fail, generally by: excessive plastic flow, fracture, or delamination of the coat from its substrate. In this work, perfect interface between layer and substrate was considered. We have done a two-dimensional analysis, using finite element method, of the stress distribution arising when a plane coated body is subjected to a contact load by an elastic cylindrical indenter. We consider normal and tangential force. Both, substrate and indenter were made of Steel. Three different types of material were used as a coating: brass, ceramic and Steel. The last one was used for validation. The results are used to investigate the influence in the field stress from layer thickness, properties of the coating materiais and the friction coefficient that acts between the indenter and coating. The results show that there is an optimum thickness when the substrate is coated with ceramic. In this case, the substrate is more protected by the layer.